PENGARUH PRENATAL GENTLE YOGA PADA IBU HAMIL TRIMESTER III TERHADAP KEJADIAN RUPTUR PERINEUM PADA PERSALINAN NORMAL - Sherly Dwi Gustiya; Ni Made Gita Gumangsari; Isviyanti Isviyanti (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2025)
In West Nusa Tenggara Province, the leading cause of maternal death was bleeding, with 27 cases. Perineal rupture or laceration is an obstetric tear that occurs in the perineal area, caused by the inability of the pelvic muscles and soft tissue to accommodate the birth of the baby. Prenatal gentle yoga can help in many ways, one of which is preventing long-term damage to the body and helping the birthing process. The aim of this study was to prove the effect of prenatal gentle yoga in third trimester pregnant women on the incidence of perineal rupture during normal delivery. Another study conducted to identify perineal rupture during childbirth showed that the group who did yoga during pregnancy did not experience perineal rupture. The research method that will be used is One Shot Case Study. The product that will be produced from this research is a Prenatal Gentle Yoga Module which contains prenatal gentle yoga movements for pregnant women in the third trimester to prevent perineal rupture during normal childbirth. 1 as many as 5 people (16.66%) and experienced 2nd degree perineal rupture as many as 2 people (6.66%) while respondents who did yoga 4 times during the third trimester of pregnancy did not experience perineal rupture as many as 18 people (60%) and experienced There were 5 people (16.66%) with grade 1 perineal rupture, but there were no respondents who experienced grade 2 perineal rupture. It can be concluded that there is a significant influence between prenatal gentle yoga and the incidence of perineal rupture in normal delivery with a p value of 0.000.